Political Communication Strategy of The General Election Supervisory Agency of Karimun District in Legislative & Presidential Election in 2024 - Khairunnisa; Nugroho, Catur (Indonesian Journal of Social Science Research, 2024)
Elections are one of the most important democratic processes in Indonesia. This study aims to examine more deeply the political communication carried out by Bawaslu Karimun Regency in the 2024 legislative & presidential elections. This research uses a qualitative research approach with a constructivist paradigm and data collection by collecting data with interviews and documents. The study uses descriptive analysis methods through library research. The research identifies problems to ensure elections are fair, transparent, and free from various forms of manipulation or violations. The analysis includes communication and situation analysis, namely cooperation with the media to fight hoaxes, provide accurate information, and oversee elections transparently. The implementation and monitoring of communication strategies are critical to maintaining integrity and transparency in general elections. The evaluation and re-planning of the communication strategy is an important step to assess performance and identify areas for improvement.